Effects of obesity on the course of inflammatory bowel disease. Issue 1 (2nd January 2019) - Pavelock, Natalie; Masood, Umair; Minchenberg, Scott; Heisig, David
Abstract: Obesity is increasingly common among patients with inflammatory bowel disease (IBD). The interplay between proinflammatory states of obesity and the course of IBD is yet to be elucidated. We conducted a retrospective study of 55 patients with IBD over the course of 5 years (2012 to 2017). We documented various clinical outcomes (mean number of clinic visits, hospitalizations/flares, procedures, and escalations in therapy) based on three initial weight groups: normal weight, overweight, and obese. There was an increasing trend in all clinical outcomes with increasing weight and a statistically significant difference in mean clinic visits ( P = 0.048) and mean hospitalizations/flares ( P = 0.004) when comparing normal-weight to obese individuals. Our study suggests that obesity influences burden of disease and treatment in IBD. This should encourage clinicians to treat obesity in IBD patients as an active problem because it may help improve clinical outcomes.